2007
DOI: 10.1007/s00520-007-0222-2
|View full text |Cite
|
Sign up to set email alerts
|

Personality and fatigue in patients with benign or malignant breast disease

Abstract: Goals of work The aim of the study was to examine the role of five general personality traits in fatigue in a group of patients with breast cancer (BC) and a group with benign breast problems (BBP). Materials and methods Of the 304 participating women, 127 patients had BC and 177 BBP. A fatigue scale was completed before diagnosis and 1, 3, and 6 months after diagnosis (benign patients) or surgical treatment (BC patients). A personality questionnaire (NEO-FFI) and a depression scale (CES-D) were completed befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 30 publications
4
33
0
1
Order By: Relevance
“…In accordance with previous studies [26], a lower score on the personality factor extraversion (i.e., higher score on introversion) also predicted fatigue in the BC group. Michielsen et al [26] provided the following two explanations for the relationship between extraversion and fatigue.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In accordance with previous studies [26], a lower score on the personality factor extraversion (i.e., higher score on introversion) also predicted fatigue in the BC group. Michielsen et al [26] provided the following two explanations for the relationship between extraversion and fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…As was already found in earlier studies [22,26,29], neuroticism predicted fatigue, but only in the BBP group in the present study. Although patients in the BBP group did not receive treatment that could induce fatigue, patients in this group who scored higher on neuroticism reported more fatigue.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Millar et al [16] found that neuroticism was a (minor) predictive factor for psychological morbidity 1 year after treatment for breast cancer. Two studies reported significant associations between neuroticism and long-term symptoms of fatigue after breast cancer surgery [36,46]. Neuroticism has also been found to be associated with a greater risk for depressive symptoms among breast cancer patients after primary surgical treatment [34].…”
Section: Psychological Predictorsmentioning
confidence: 99%